Secular trends of blood pressure, body mass index, lipids and fasting glucose among children and adolescents in Turkey - (:unkn) unknown (My University, 2011)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT: •  Turkey is in a state of rapid transition and urbanization. There is ample evidence for an increased cardiovascular risk over the past two decades in Turkey. •  Obesity, dyslipidemia and high blood pressure in children are markers of the future burden of cardiovascular disease and clustering of cardiovascular risk factors starts early in life. •  The patterns of cardiovascular risk factors in populations are not static over time and the secular trends in obesity and cardiovascular risk factors among children and adolescents of developing countries have not been completely defined. WHAT THIS STUDY ADDS: •  The prevalences of obesity and high blood pressure have increased several folds among Turkish children and adolescents over the past two decades. •  The temporal trends in fasting glucose and lipids did not correlate with the increasing prevalence of obesity with the exception of HDL-C levels. •  Finally, the prevalence of metabolic syndrome has doubled in Turkish children and adolescents over the last two decades. Our findings indicate that there may be an increase in the future morbidity and mortality from cardiovascular disease, thrombosis, stroke and diabetes mellitus throughout the developing countries. SUMMARY: Patterns of cardiovascular risk factors and metabolic syndrome risk criteria in populations are not static over time. We analyzed the trends in lipid levels, blood pressure, fasting glucose and body mass index over the last two decades among children and adolescents. Two different cross-sectional studies were examined among students (ages 8-18) in 1989 (n = 1385) and in 2008 (n = 1746). Using the international cut-off points and percentiles, we identified children and adolescents with elevated blood pressure, triglycerides, fasting glucose (≥100 mg dL(-1) ), body mass index and low high-density lipoprotein cholesterol (HDL-C) levels. The prevalence of obesity has increased several folds over the last two decades. According to the international criteria, 4.3% of children were obese and 15.2% were overweight in 2008 vs. only 0.6% obese and 4.3% overweight in 1989 (P < 0.001). The prevalence of elevated systolic blood pressure also increased significantly among 8-12-year-old boys and girls (28.5 vs. 15.7%, P < 0.001). The temporal trends in fasting glucose and lipids did not correlate with the increasing prevalence of obesity with the exception of HDL-C levels. Low HDL-C (≤ 10th percentile) was observed in 16.3% in 1989 vs. 21.6% in 2008 (P = 0.016). HDL-C levels decreased significantly among adolescent boys. Finally, the prevalence of metabolic syndrome by modified National Cholesterol Education Program (NCEP) criteria has doubled over the last two decades (2.2 vs. 4.5%, P < 0.001). Strategies for combating the future cardiovascular mortality should focus on the prevention of obesity, high blood pressure and metabolic syndrome among children and adolescents.
Keywords: Cardiovascular risk factors; children and adolescents; lipids; secular trends